1991
DOI: 10.1161/01.res.69.6.1538
|View full text |Cite
|
Sign up to set email alerts
|

Altered calcium handling in left ventricular pressure-overload hypertrophy as detected with aequorin in the isolated, perfused ferret heart.

Abstract: The purpose of this study was to test the hypothesis that systolic and diastolic dysfunction in left ventricular pressure-overload hypertrophy is caused by abnormal intracellular calcium handling. Experiments were performed with intact, buffer-perfused, isovolumic ferret hearts (n=9 hypertrophied, n=9 control) that were loaded with the bioluminescent indicator aequorin to monitor changes in cytoplasmic calcium. In each experiment, left ventricular pressure and intracellular calcium transients were simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…At the end of the experiment, the heart was perfused with a 50 mM 95% Ca 2ϩ -5% Triton X-100 solution, which lysed the cells and exposed the remaining aequorin to high amounts of Ca 2ϩ (3). Luminescence signals to be converted to Ca 2ϩ signals, L, were normalized by the total light emission, Lmax, which was estimated as the integral of the aequorin signal collected during the lysis procedure multiplied by the rate constant for aequorin consumption (2.11/s) (3).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, the heart was perfused with a 50 mM 95% Ca 2ϩ -5% Triton X-100 solution, which lysed the cells and exposed the remaining aequorin to high amounts of Ca 2ϩ (3). Luminescence signals to be converted to Ca 2ϩ signals, L, were normalized by the total light emission, Lmax, which was estimated as the integral of the aequorin signal collected during the lysis procedure multiplied by the rate constant for aequorin consumption (2.11/s) (3).…”
Section: Methodsmentioning
confidence: 99%
“…Saturation transfer 31P-NMR studies in the setting of myocardial hypertrophy have suggested that CK forward flux is reduced (as compared with normal) during inotropic stimulation (38). Alterations in calcium (Ca2") dynamics, and the Ca2" ATPase activities ofmyosin and the sarcoplasmic reticulum have also been described in hypertrophied myocardium, as have abnormalities ofthe mitochondrial/myofibrillar ratio and capillary to mitochondrial diffusion distances (30,(39)(40)(41). Lastly, there is evidence of a switch in substrate preference away from fatty acid utilization and toward glucose in hypertrophied myocardium (33,(42)(43)(44).…”
Section: Myocardial Bloodflow Myocardial Blood Flows Measuredmentioning
confidence: 99%
“…The spontaneously hypertensive rat (SHR) is a model that in many respects parallels the course of human hypertensive heart disease. Studies of both failing human 13 and hypertrophied and failing SHR 4 -5 myocardia reveal altered calcium transients and impaired force development; however, the possible role of altered intracellular calcium handling in the development of depressed contractile function during the transition from compensated hypertrophy to failure remains unclear. Recent isolated muscle studies have demonstrated differences systolic pressure, and ±dP/dt fell in SHR-F hearts.…”
Section: Effects Of Treppe and Calcium On Intracellular Calcium And Fmentioning
confidence: 99%
“…The spontaneously hypertensive rat (SHR) is a model that in many respects parallels the course of human hypertensive heart disease. Studies of both failing human 13 ], and pressure decrease in parallel in the SHR-F heart with increasing stimulation rate, suggesting that impaired calcium cycling may contribute to compromised pump function in the SHR-F heart. (Hypertension.…”
mentioning
confidence: 99%